1985
DOI: 10.2307/3281908
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular Carbohydrates of Three Nematode Species and Chemoreception by Trichostrongylus colubriformis

Abstract: The cuticle of Haemonchus contortus, Nippostrongylus brasiliensis and Trichostrongylus colubriformis contained N-acetylgalactosamine and N-acetylglucosamine, based on the binding of fluorescein-labelled lectins. Binding of the lectins varied between the sexes and body regions of the nematodes. Treatment of male T. colubriformis with the lectin Lens culinaris agglutinin (LcA) reduced the feeding by helminths that was stimulated by histamine and the male's response to their female's pheromone, based on in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 7 publications
0
13
3
Order By: Relevance
“…Many studies have shown the presence of carbohydrates on GIN surfaces, using labeled lectins (BONE;BOTTJER, 1985;PALMER;McCOMBE, 1996;JURASEK et al, 2010;HILLRICHS et al, 2012). In these studies, Concanavalin A (ConA), Lens culinaris agglutinin (LCA), Maclura pomifera agglutinin (MPA), peanut agglutinin (PNA) and Pisum sativum agglutinin (PSA) were bound to the egg surfaces, suggesting the presence of glucose, mannose and galactose carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the presence of carbohydrates on GIN surfaces, using labeled lectins (BONE;BOTTJER, 1985;PALMER;McCOMBE, 1996;JURASEK et al, 2010;HILLRICHS et al, 2012). In these studies, Concanavalin A (ConA), Lens culinaris agglutinin (LCA), Maclura pomifera agglutinin (MPA), peanut agglutinin (PNA) and Pisum sativum agglutinin (PSA) were bound to the egg surfaces, suggesting the presence of glucose, mannose and galactose carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Lectin binding to adult H. contortus has been reported by Bone and Bottjer (1985), but there appear to be no similar studies on T. circumcincta. Some of the 19 lectins used in the present study were also used by Bone and Bottjer (1985), although many lectins were not included in both experiments.…”
Section: Eggsmentioning
confidence: 86%
“…Some of the 19 lectins used in the present study were also used by Bone and Bottjer (1985), although many lectins were not included in both experiments. There was strong binding of some lectins with affinities for GalNAc, Gal and GlcNAc to adult T. circumcincta (Table 2) and also to H. contortus in both studies; however, PTL, which also recognises some α-GalNAc-containing structures, did not bind to either worm.…”
Section: Eggsmentioning
confidence: 99%
See 2 more Smart Citations